Diagnostic performance of knee physical exam and participant-reported symptoms for MRI-detected effusion-synovitis among participants with early or late stage knee osteoarthritis: data from the Osteoarthritis Initiative - Berlinberg, A.; Ashbeck, E. L.; Roemer, Frank; Guermazi, A.; Hunter, D. J.; Westra, J.; Trost, J.; Kwoh, C. K. (Osteoarthritis and Cartilage, 2019)
OBJECTIVE: Evaluate the diagnostic performance of knee physical exam findings and participant-reported symptoms for MRI-detected effusion-synovitis (ES) among knees with early and late-stage osteoarthritis (OA). DESIGN: The Osteoarthritis Initiative (OAI) is a longitudinal study of participants with or at risk for knee OA. Two samples with MRI readings were available: 344 knees with early OA (312 participants) and 216 with late-stage OA (186 participants). Trained examiners performed bulge sign (BS) and patellar tap (PT) exams, and participants reported on knee swelling and pain with leg straightening. Effusion-synovitis on 3T non-contrast MRI was scored using the MRI Osteoarthritis Knee Score (MOAKS). Diagnostic performance of physical exam findings and symptoms was estimated with bootstrapped confidence intervals. RESULTS: For the early OA sample, the highest sensitivity for medium/large effusion-synovitis was achieved with a positive finding for any of the physical exam maneuvers and/or participant-reported symptoms (81.0 [95% CI: 70.0, 91.3]). Both knee symptoms in combination had a prevalence of 11.7% and yielded the highest estimated positive predictive value (PPV) (50.0 [95% CI: 34.2, 66.7]) and likelihood ratio positive (LR+) (5.2 [95% CI: 2.9, 9.7]). In late-stage OA knees, exam findings and symptoms provided minimal information beyond the prevalence. CONCLUSION: Patient report of both symptoms, or at least one positive exam finding and at least one symptom, could be used to identify knees at increased risk of effusion-synovitis in knees with early stage OA, either for screening purposes in clinical evaluation, or for study sample enrichment with an inflammatory phenotype; diagnostic performance was not sufficiently high for clinical diagnostic purposes.
EVALuna2:36227